Study of ankle reflex grades in protein energy malnourished children aged between 1 and 5 years - Ukil, Protiksha; K, Siva Ram Prasad; T, Usha Rani; S, Srikanth (Indian Journal of Child Health, 2022)
Background: Malnutrition among children is a major health issue throughout India and South East Asia presenting with stunting and wasting. Many research studies have been conducted to establish the signs, symptoms, corresponding effects of malnutrition on child health, growth, and development. Objective: The objective of the current study is to find a difference in grading of Ankle reflex between children with Protein Energy Malnourishment (PEM) and normal healthy subjects. This will help draw a conclusive relationship between hyporeflexia and PEM. Methods: The study design is an observational case-control type of study conducted in two teaching hospitals in India. Cases of PEM (n = 30), children with Mid Upper Arm Circumference (MUAC) <12.5 and weight for height Z score (WHZ) score of lesser than -2 along with control group of normal healthy children (n = 30), all aged between 1 and 5 years were selected for the study. Ankle reflexes were noted using a simple knee hammer on 3 consecutive days of cases and control group, graded based on the NINDS Reflex Grading Scale to determine any differences between cases and controls. Results: A Chi-square test was performed and a P value result of 0.002 was obtained rejecting the null hypothesis which states that there is no relation between ankle reflex grades and presence of malnutrition. Conclusion: A conclusion could be drawn where a significant association was observed between lower ankle reflex grades and cases of PEM as compared to those noted in the control group. The Achilles Tendon reflexes obtained from cases was significantly reduced. Eliciting the Deep Tendon reflexes and drawing a relation with PEM children can be used as an initial diagnosis for neurological deficits associated with PEM.